Molecular Pathogenesis of Atherosclerosis and Implication for Therapy - AP, Jeanne (IIUM Medical Journal Malaysia, 2010)
A growing body of evidence supports the role of infl ammation in the pathogenesis of atherosclerosis. However, the supposed initiation factors of atherogenesis are infection and change in shear stress on certain location, leading to attachment of LDL and subsequent oxidation. The pathway activated are the NFkB and TGFβ leading to endothelial dysfunction and production of infl ammatory cytokines and adhesion factors followed by recruitment of infl ammatory cells to the site, oxLDL internalization and foam cell formation in the fatty streak that later develop into atherosclerotic plaque. Further, p53signaling causes apoptosis leading to plaque rupture, platelet activation and aggregation ending in clinical manifestations. Moreover, numerous individual risk factors might aggravate the condition, and the progress might take decades depending on the balance of pro and anti atherogenic factors. Therefore, management of atherosclerosis addressing the individual risk factors using drugs with various properties coping with the molecular basis especially infl ammation is beneficial.